DINAMIKA PERDAGANGAN BERAS VIETNAM - Agus Dwi Nugroho; Jamhari Jamhari; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
The aims of this study is to analyze the performance of export-import, competitiveness and the factors affecting export-import of Vietnam rice. Type of data used is secondary data of 1980-2009. To determine the fluctuation of export-import trade were applied trend and trade specialization ratio. To find out the analysis of competitiveness were run revealed comparative advantage (RCA) and acceleration ratio (AR). To investigate the factors affecting the export and import used error correction model (ECM). Vietnam export trend showed an increase and imports trend showed a decline and in the maturity stage. Vietnam has high competitiveness but the exports acceleration is low. Vietnam’s export affected by per capita rice availability and the exchange rate while imports of Vietnam affected by the production, world rice prices and real national income.